Comparison of Factors Related to Accounting Students’ Minor Course Selection: An Exploratory Study at Walailak University - Saramolee, Alisara; Srisuwan, Praphada; Suwangerd, Ratchada; Sawangarreerak, Siriporn; Lakkanawanit, Pankeawta (WMS Journal of Management, 2020)
This study sought to explore factors influencing students’ decision to select a minor course in accounting program at Walailak University using an online questionnaire to collect data from 180 participants. A factor analysis was first employed to identify the factors. The t-tests, One-way ANOVA, and correlation analysis were used to compare the factors. Results showed that opportunity in labor market and liking and interest in course were the two statistically significant factors. When comparing personal data, men expressed their concern about personality and aptitude more than women. Students receiving higher grade in fundamentals of accounting subject were more motivated by liking and interest in course. In addition, GPAX of students was found to have a significant positive relationship with liking and interest, opportunity in labor market, personality and aptitude, and quality of life as well. These findings suggested that minor courses in accounting program should be developed based on career choices and passion of students. Teachers’ ability and their techniques to create highly effective learning environment including their suggestion are also crucial for students.